Uso de aerofotos disponíveis em acervos públicos: algumas aplicações a partir do acervo CPRM/DNPM - SILVA, Larissa Nascimento Fanjas da (2022)
Aerophotogrammetry has been used for more than a century by researchers who find it difficult to carry out surveys in areas of difficult access, with a great emphasis on archeology, environmental engineering, ecology, forestry, geography, meteorology, military intelligence, natural resources management, oceanography, soil and urban and regional planning. In the Amazon, and specifically in the State of Pará, Brazil, it is possible to find several private companies and government institutions that use aerial photogrammetry to obtain images in which they can capture information from a certain area. In addition, some aerial photo collections are even available for use free of charge, such as the collection of aerial photos from the 1960s and 1970s of the National Department of Mineral Production (DNPM), which according to the same, these decades have a wide coverage in the state of Pará due to the RADAM project that carried out data collection on mineral resources, soils, land use and cartography in the Amazon. Thus, the present work aims to show the possible applications of aerial photographs made available by the National Department of Mineral Production in the 1960s and 1978 in line with an updated image through the CBERS 04A satellite, available free of charge in the INPE image catalog. – National Institute for Space Research, and then carry out the photointerpretation of the images and develop the cartographic products. Through the method of photointerpretation of these aerial photos, it was possible to carry out multitemporal analyzes of urban expansion and land use and cover, applying the method of interpretation keys, which is of direct intrinsic character to facilitate the identification of the imaged objects quickly and accurately. Based on the results, it was possible to identify a change in the characteristics of the study area between the years 1960, 1978 and 2021, caused by human interventions. Furthermore, in relation to vegetation cover, it was possible to observe the decrease of the ombrophilous forest, due to the degradation of the vegetation, which shows a significant deforestation in the area. The expansion of the urban area was also a notable factor, increasing significantly over the years.